THE ISSUES OF IMPLEMENTING ISLAMIC QUALITY MANAGEMENT SYSTEM MS1900:2005 CERTIFICATION AT THE DEPARTMENT OF AWQAF, ZAKAT AND HAJJ (JAWHAR) - Ali, Hasliza Mohamad; Basir, Siti Arni; Ahmadun, Musaiyadah (Online Journal of Research in Islamic Studies, 2015)
MS 1900:2005 is the current quality system in the world standard of certification based on Syari’ah in collaboration of the Department of Standards Malaysia with SIRIM, IKIM and other agencies to search the suitability of MS ISO 9001 from Islamic perspectives with the purpose to modify the needs of MS ISO 9001 that do not conform to the Islamic law. There are 27 organisations successfully applying for this certificate until today where JAWHAR is the first government department that obtain MS 1900:2005 certificate in Malaysia. The objective of this research is to look in depth of the issues faced by JAWHAR in the implementation of MS1900:2005. This is qualitative research which involved a case study of JAWHAR. The semi-structured interviews were conducted with 10 interviewees involving the top management, JAWHAR executives and administrative assistants. The data was analysed by using thematic analysis method to identify the issues faced by Department of Awqaf, Zakat and Hajj (JAWHAR) in the implementation of MS1900:2005. The result shows that the management of Department of Awqaf, Zakat and Hajj (JAWHAR) is facing few issues in the implementation of MS1900:2005 especially in determining Syari’ah scope, staff management and to maintain MS 1900:2005 certification.